Teaching Reading by Using Jumble Summary Strategy - Gustriani Novita Sari; M Arif Fadli (Vivid: Journal of Language and Literature, 2019)
Reading is the process of knowing, understanding, and getting information about the contents of the text. Teaching Reading is the process of teaching students to understand and comprehend texts. There are some problems in teaching reading. Therefore, the teacher needs to implement several strategies. One strategy is the Jumble Summary strategy. This is a strategy used by the teacher to present key words and phrases that are randomly ordered from the lesson or topic to students. Students place terms and phrases in paragraphs or logical sequences to show understanding. This research is an experiment. The population of this research is the eighth-grade students of SMPN 2 Suliki District. There are 6 classes in the school. A cluster sampling technique is used to determine the sample. Experimental classes are taught with the Jumble Summary Strategy, and the control class is taught by the strategies currently used by the teacher. This research tool is a multiple-choice reading test. This test is validated because the material is taught to students before taking the test. To check the reliability of the test, researchers used a half-separate test formula. After that, the data were analyzed using the t-test formula suggested by Gay, Mills, and Airasian [1]. From the data analysis, the t-count is 3.214, while the t-table is 2.021, which means that the t-count is greater than the t-table. In other words, the research hypothesis is accepted. So it can be concluded teaching reading by using the Jumble Summary Strategy has had a significant influence on learning to read. Therefore, it is recommended that English teachers apply the Jumble Summary Strategy in reading learning.